-10n+7=-18-5n

Simple and best practice solution for -10n+7=-18-5n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10n+7=-18-5n equation:


Simplifying
-10n + 7 = -18 + -5n

Reorder the terms:
7 + -10n = -18 + -5n

Solving
7 + -10n = -18 + -5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5n' to each side of the equation.
7 + -10n + 5n = -18 + -5n + 5n

Combine like terms: -10n + 5n = -5n
7 + -5n = -18 + -5n + 5n

Combine like terms: -5n + 5n = 0
7 + -5n = -18 + 0
7 + -5n = -18

Add '-7' to each side of the equation.
7 + -7 + -5n = -18 + -7

Combine like terms: 7 + -7 = 0
0 + -5n = -18 + -7
-5n = -18 + -7

Combine like terms: -18 + -7 = -25
-5n = -25

Divide each side by '-5'.
n = 5

Simplifying
n = 5

See similar equations:

| 7.7=(2.1-7m) | | 13.5/3 | | -18n+18=-16n-2 | | 1/2x-5=13 | | 1*x=27/5 | | 140=15x+20 | | 4+x=2x+18 | | x^1*x^9-x^2= | | z^5+5z=-4 | | -7x(x-5)= | | (a+9)(a+3)=72 | | p(x)=(7x^5+3x^3-50)(9x^8-8x^1) | | 2t^2-5=11 | | 10-p=28 | | 6x-(-7x+36)=16 | | y=19.54+28.73x | | p+10=3p | | ^3sqrt(27x^5y^6)/216 | | X^2-.36=0 | | 5-r=2+2r | | 6x(2x-3)=4(3x^2+9) | | 4p+56=5p+41 | | 1-X/4x-1=-3/4 | | -2(7x+30)=18+2x | | cx+d=0 | | 12.5x=50000+100x-0.05x^2 | | (1/2x3)(4x-5) | | 3u+1=2 | | 3(4x+5)=22-4x | | 3/6×2/3 | | 1/6=10/x | | 4x-6=40x+21 |

Equations solver categories